Risk factors of low peak bone mass in Indonesian women - Ray Sugianto; Johana Titus; Minarma Siagian (Jurnal Gizi Klinik Indonesia, 2014)
Background: Osteoporosis occurred in 64% of Indonesian women aged 60-64 years. The risk of osteoporosis can be reduced by achieving optimal peak bone mass in ages 25-32 years. However, 33.4% women had low peak bone mass (LPBM).Objective: We aimed to develop a tool to identify women at risk of developing LPBM in order to ameliorate this situation. Some risk/protective factors were explored in a case-control study.Method: We recruited 25 cases, those with LPBM (T-score <1) according to peripheral bone densitometry and 25 controls from Cengkareng District, West Jakarta. They were assessed using questionnaires to explore their historical intake of calcium, tea/coffee, and weight-bearing activity. We also measured BMI and body composition. Parameters among case and control groups were analyzed using independent T-test or Mann-Whitney, and odds ratio in relation to peak bone mass was also computed.Results: Between cases and controls, there were no differences observed in BMI, body composition, weight-bearing activity, and historical tea/coffee consumption. Calcium intake from sources other than milk and its derivatives were also found not to differ. Historical calcium index (HCI), measuring weekly calcium intake since childhood, was found lower in cases (median=160 vs 965; p=0.001). HCI cut-off analysis found that the values of 300 and 1000 yielded good specificity (80%) and sensitivity (92%) for LPBM. OR analysis identified those with HCI <1000 (OR=0.61; 95% CI: 2.05−54.95) as at moderate risk of developing LPBM, and HCI ≤ 300 as at higher risk.Conclusion: We concluded that, as low HCI was the risk factor for developing LPBM, calculation of HCI should be done to earlier identify women at risk, thus prompting earlier nutrition and lifestyle intervention to prevent the occurrence of LPBM and future osteoporosis.